Effect of Technology Organization Environment Framework in Business Strategy on Decision Making of Small and Medium Enterprises in Lagos, Nigeria - Aina, Adeola Temitope (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2025)
This study examined effect of Technology Organization Environment (TOE) framework in business strategy on decision making of small and medium enterprises (SME) in Lagos-Nigeria. Using the TOE framework, the research explored how technological, organizational, and environmental factors influence business strategy. A quantitative approach was employed, with data collected from 350 SME managers through a structured questionnaire. The analysis using descriptive statistics and multiple linear regression revealed several key factors influencing the adoption of TOE framework. Operational efficiency and competitive advantage were identified as significant drivers of adoption of TOE. On the other hand, limited technical expertise, high implementation costs, and lack of awareness emerged as major barriers. The model demonstrated strong predictive power, capturing a substantial portion of the variance in data in technology-organization environment adoption. The findings underscored the need for targeted interventions, such as training programs, cost-effective tools, and awareness campaigns, to enhance adoption among SMEs. This study contributes to the literature by providing empirical evidence on the factors influencing TOE adoption in a developing economic context and offers practical recommendations for SMEs, policymakers, and stakeholders.